2009
DOI: 10.1192/bjp.bp.108.055798
|View full text |Cite
|
Sign up to set email alerts
|

Lithium levels in drinking water and risk of suicide

Abstract: Although lithium is known to prevent suicide in people with mood disorders, it is uncertain whether lithium in drinking water could also help lower the risk in the general population. To investigate this, we examined lithium levels in tap water in the 18 municipalities of Oita prefecture in Japan in relation to the suicide standardised mortality ratio (SMR) in each municipality. We found that lithium levels were significantly and negatively associated with SMR averages for 2002-2006. These findings suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
148
4
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(171 citation statements)
references
References 5 publications
8
148
4
7
Order By: Relevance
“…In some regions of the world, [7,9] in order to increase the daily intake of lithium in human nutrition, lithium is added as a supplement in the potable water (tap water), with the fi nal concentration of lithium in water of 170 μg/L. Low lithium concentration in potable water from multiple public water supply systems from the network in the Republic of Macedonia points to the possibility for a beginning of the enrichment of Macedonian potable water with lithium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some regions of the world, [7,9] in order to increase the daily intake of lithium in human nutrition, lithium is added as a supplement in the potable water (tap water), with the fi nal concentration of lithium in water of 170 μg/L. Low lithium concentration in potable water from multiple public water supply systems from the network in the Republic of Macedonia points to the possibility for a beginning of the enrichment of Macedonian potable water with lithium.…”
Section: Resultsmentioning
confidence: 99%
“…[10] The obtained results [ Research shows that concentration of lithium in the potable water, surface water, water from wells boreholes and mineral water from the territory of Republic of Macedonia is in accordance with the relevant international values for the content of lithium in water. [7,11] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiological studies have shown the inverse association of lithium levels in tap water and suicide rates [1][2][3][4][5][6], although a few studies failed to find such association [7] or have reported an ambiguous association [8]. However, many people drink both mineral water and tap water.…”
Section: Introductionmentioning
confidence: 99%
“…After almost 70 years of medical research, lithium salts have been shown effective for the protection against mania and depression, especially in the acute and long-term management of bipolar disorder 2 , and reducing both suicide and mortality in mood disorders 3,4 . More recently, new biological properties of lithium have been discovered, considering the drug for a pharmacological option for neurodegenerative and spinal cord disorders such as Alzheimer's disease 5 , amyotrophic lateral sclerosis 6 and chronic spinal cord injuries 7 .…”
Section: Introductionmentioning
confidence: 99%